X+9=3x+23

Simple and best practice solution for X+9=3x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+9=3x+23 equation:



X+9=3X+23
We move all terms to the left:
X+9-(3X+23)=0
We get rid of parentheses
X-3X-23+9=0
We add all the numbers together, and all the variables
-2X-14=0
We move all terms containing X to the left, all other terms to the right
-2X=14
X=14/-2
X=-7

See similar equations:

| 6(m+4)-5(m+3)=6 | | X÷3+x÷=10 | | 2x-x-2/2=x/3-6 | | 2x^=x+3+18 | | a=450/5 | | (x)/(3)-1=(x)/(5)+3 | | x/3-1=x/5+3= | | 13x-14=-40 | | 7x-8x+5x=2+4 | | 12(n)=n^2 | | x=$5824/1.04 | | 27y+15=-18y-6 | | (7x-8)^2=-81 | | 27y+15=-18y-7 | | –4.9x^2+19.6x+58.8=0 | | 0=–4.9x^2+19.6x+58.8 | | 0=–4.9t2+19.6t+58.8 | | 13(n)=n^2 | | -3/4=t+1/2 | | -2(v+5)=-4v+8 | | -8=-5w+3(w-6) | | 5v+45=-9(v+9) | | 29.6t=207.2 | | 0.1-x=0.45x | | 0.1-x=0.315x | | 3x+2=(2x+20)/2 | | 3x+2=2x+20/2 | | 1=9x+4 | | 4-(3x-3)=12x+2 | | 9y+1=0 | | -23+z=-44 | | 0.1=0.315x+x |

Equations solver categories